STUDI KOMPARASI PEDOMAN DESAIN SEBAGAI REFERENSI INOVASI DAN DESAIN BENDUNGAN BETON GRAVITY - Jumadil Syam (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2022)
Concrete gravity dams continued to develop in Indonesia even though the population is still smaller than embankment dams. Until 2021 there consist of 16 concrete gravity dams or about 7% of all dams in Indonesia. The utilization of concrete gravity dams in Indonesia is 75% for hydropower or as many as 12 dams. Concrete gravity dam is a high-risk structure so the design of concrete gravity dams must be referred to the guidelines where applicable in Indonesia and internationally with approval from Dam Safety Organization. In Indonesia, the construction of concrete gravity dams cannot be separated from the participation of design consultants from developed countries such as the UK, Japan, US, Canada, Korea, and China. Indonesian Water Resource Guidelines 2009 is formal reference that must be adhered to by all design and construction planners in Indonesia, so that designs that refer to the guidelines and manuals from foreign countries must go through a comparison and evaluation process to meet the design acceptance criteria in accordance with the Indonesian Water Resource Guidelines 2009. Comparison processes include load conditions, design concepts, seismic analysis methods, stability and stress analysis methods, and stability and stress acceptance criteria. As a results of comparison, we can get information that the Indonesian Water Resource Guidelines 2009 apply stability and stress acceptance criteria more conservative. As consequence, the investment cost for the construction of concrete gravity dams in Indonesia is becoming more expensive.Keywords: dams, concrete gravity, guidelines, comparation, stability.